SECURITY SYSTEM ON WIFI NETWORKS BASED ON RSS (RECEIVED SIGNAL STRENGTH) CORRELATION - Tristianto, Didik (International Journal of Business and Information Technology, 2025)
Communication systems are always evolving, including data communication that occurs wirelessly, such as through WIFI networks. However, wireless communication inherently has a low level of security, making it vulnerable to attacks from unauthorized parties. In this research, a security system for WIFI networks was created based on the correlation of RSS (Received Signal Strength) values obtained through a channel probing process between two PCs by implementing several scenarios. The RSS data was quantized using Aono's method to obtain binary bits of 1 and 0. From the test results, it can be seen that the Key Generation Rate (KGR) produced was 16bit/s for a 50ms time interval, 8bit/s for 110ms, and 7bit/s for 120ms. The Key Disagreement Rate (KDR) was 30% for 50ms, 46.59% for 110ms, and 46.71% for 120ms, where the two PCs had a high bit difference. However, with Linear Block Code, the KDR value could be reduced to 0%. From the randomness results, it has met the randomness requirement for 50ms, which is 0.3712. From the identical bits between the two PCs, a symmetric key can be generated, meaning the key on PC1 and PC2 is the same.